Prospective long-term study of outcomes of 100 arteriovenous fistulas in patient with chronic renal failure - Panchal, Mithun (International Surgery Journal, 2018)
Background: This study describes the experience of arteriovenous fistula (AVF) creation as vascular access for haemodialysis. Methods: This study has been carried out in our hospital from January 2004 to December 2016. A total of 154 AVFs were created in 100 patients. Maximum follow-up was 2 years, and minimum was 6 months. Results: In this study of 100 cases of AVFs, primary patency rates by Kaplan Meier analysis showed 78.81% patency of fistulas at the end of 1 year and patency dropped to 14.81% at the end of 5 years. The primary failure rate was 21.2%. Basilic vein was used in 26.35% cases, cephalic vein in 63.5%, and antecubital vein in 9.75% cases. On table, bruit was present in 134 (90.9%) and thrill in 126 (89.3%) cases. During dialysis, flow rate >250ml/min was obtained in 40(29.9%) cases. In complications, 2 (0.4%) patients developed distal oedema. Conclusions: Presence of on table thrill and bruit are indicators of successful AVF. If vein diameter is <2mm, chances of AVF failure are high. Flow rates in patients with vein diam. More than 2mm was significantly higher as compared with patients with vein diam. Less than 2mm (P< 0.001). Flow rates are higher in non-diabetic patients as compared to diabetic patients (P <0.001). Average blood urea and serum creatinine values are significantly lesser in patients undergoing dialysis through successful fistulas as compared to patients with failed fistulas. Correspondingly, incidence of deaths is significantly lesser in patients with successful fistulas. During proximal side-to-side fistula between antecubital/basilic vein and brachial artery, dilating of the first valve toward wrist helps to develop distal veins in the forearm by retrograde flow. This technique avoids requirement of superficialization of basilic vein in the arm.